2021
DOI: 10.3390/cryst12010038
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Fabricating Wurtzite AlN Film on (0001)-Plane Sapphire Substrate

Abstract: Ultrawide bandgap (UWBG) semiconductor materials, with bandgaps far wider than the 3.4 eV of GaN, have attracted great attention recently. As a typical representative, wurtzite aluminum nitride (AlN) material has many advantages including high electron mobility, high breakdown voltage, high piezoelectric coefficient, high thermal conductivity, high hardness, high corrosion resistance, high chemical and thermal stability, high bulk acoustic wave velocity, prominent second-order optical nonlinearity, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 124 publications
0
13
0
Order By: Relevance
“…[4,15] AlN crystals can be grown by a wide range of different techniques such as physical vapor transport (PVT), metalorganic vapor phase epitaxy (MOVPE), physical vapor deposition (PVD), and hydride vapor phase epitaxy (HVPE). [2,16] Recently, the recrystallization of submicron thick AlN/sapphire templates using hightemperature annealing (HTA) has gained a lot of interest as a means of manufacturing epitaxial layers with a very high crystallinity. These thin layers are typically deposited using PVD or MOVPE processes and afterward recrystallized at high annealing temperatures of up to 1700 °C, as first introduced by Fukuyama et al, who employed an N 2 -CO atmosphere to prevent decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…[4,15] AlN crystals can be grown by a wide range of different techniques such as physical vapor transport (PVT), metalorganic vapor phase epitaxy (MOVPE), physical vapor deposition (PVD), and hydride vapor phase epitaxy (HVPE). [2,16] Recently, the recrystallization of submicron thick AlN/sapphire templates using hightemperature annealing (HTA) has gained a lot of interest as a means of manufacturing epitaxial layers with a very high crystallinity. These thin layers are typically deposited using PVD or MOVPE processes and afterward recrystallized at high annealing temperatures of up to 1700 °C, as first introduced by Fukuyama et al, who employed an N 2 -CO atmosphere to prevent decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the crystallinity of AlN/Al 1−x Sc x N, several methods can be used for film growth. Single-crystal AlN can be grown via physical vapor transport (PVT) on substrates up to 60 mm in diameter [ 34 , 35 , 36 ]. Single-crystal Al 1−x Sc x N can be grown by molecular beam epitaxy (MBE) [ 9 ] on 100 mm wafers [ 37 ] with scandium concentration x from 0.06 to 0.36 [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, an AlN monolayer has attracted a lot of attention as a semiconductor material with an ultra-wide band gap. [42][43][44] AlN materials have advantages such as high chemical and thermal stability, 45 high electron mobility, 46 and excellent UV transparency. 47,48 K-doped AlN nanosheets exhibit roomtemperature ferromagnetism at relatively low concentrations, according to calculations by Xiao et al 49 Ouyang et al reported the CO adsorption properties of pristine and defective h-AlN nanosheets.…”
Section: Introductionmentioning
confidence: 99%